Cultural Sustenance in Language Education: Student Responses to Indigenous Knowledge Integration in Indonesian EFL Classrooms - Markus Lesa; Nehru P. Pongsapan; Charlie Baka (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
The marginalization of Indigenous Knowledge Systems (IKS) in formal education perpetuates colonial paradigms in postcolonial classrooms, yet empirical research on integrating local epistemologies into English as a Foreign Language (EFL) instruction in Indonesia's culturally distinct regions remains severely limited. This study aims to investigate the lived experiences of eighth-grade students at SMPN 6 Sa'dan, Tana Toraja Regency, who engaged with Toraja Indigenous Knowledge Systems within EFL vocabulary instruction across an eight-week pedagogical intervention. Employing a qualitative critical phenomenological design grounded in culturally sustaining pedagogy, decolonial language education, and critical language awareness, data were generated through triangulated multimodal methods: two phenomenological interviews per participant (60–90 minutes each), 32 hours of participant observation, weekly reflexive journals, and student-produced visual artifacts. Analysis followed Braun and Clarke's (2021) reflexive thematic analysis within a critical realist framework using NVivo 14. Findings revealed five interrelated dimensions of student experience: (1) epistemological reorientation, wherein English was reconceptualized from a symbol of Western dominance to a vehicle for indigenous meaning-making through 'reverse translation' practices; (2) heritage-positive identity reconstitution, documented in 11 of 12 participants; (3) affective transformation evidenced reduction in anxiety-related lexical items in student journals; (4) emergent critical language-culture consciousness concerning linguistic imperialism and cultural untranslatability; and (5) an unanticipated intergenerational knowledge exchange, wherein students became cultural mediators initiating bilingual documentation of elder knowledge. The study contributes a transferable heritage-sustaining language pedagogy framework, challenging Western-centric pedagogies in postcolonial Indonesian classrooms and offering practical implications for curriculum design, teacher education, and language policy in Indigenous and minoritized language contexts globally.